Grammatical licensing and relative clause parsing in a flexible word-order language - Wagers, Matthew W.; Borja, Manuel F.; Chung, Sandra (Cognition, 2018)
Evidence from two experiments reveals that in Chamorro, a verb-first language, the comprehension of relative clauses (RCs) is sensitive to the order of the RC with respect to the head. Unlike most other languages, Chamorro allows both postnominal and prenominal RCs, so it is possible to compare how the two types are processed within the same language. Moreover, Chamorro is a small language whose speakers do not fit the typical profile of participants in cognitive science experiments. We found that RC comprehension is affected by the relative order of RC and head, and by other language-specific factors. However, we also found new support for a subject gap advantage in all RC types. This advantage emerged in early response measures and was reinforced in postnominal RCs, but often outcompeted in prenominal RCs by other pressures. We frame this competition in terms of a model in which grammatical licensing requirements play a key role in comprehension.